Mixed Marriages Under Indonesian Law and Its Legal Implications on Citizenship, Property, and Inheritance - Maria Pranatia; Anne Gunadi Martono Widjojo (Politeknik Siber Cerdika Internasional, 2026)
Background: Mixed marriages have become an increasingly significant legal phenomenon in line with the growing cross-border mobility of individuals. Such marriages give rise to complex legal consequences, particularly in relation to the citizenship status of children, the classification of marital property, and inheritance rights. Objective: This study aims to examine the legal framework governing mixed marriages in Indonesia and to analyze the legal implications arising from such unions. Methods: The research employs a normative juridical research method with a statutory approach, focusing on relevant laws and regulations. Results: The findings indicate that mixed marriages are recognized under Indonesian law, provided that they fulfill the legal requirements for a valid marriage. However, these marriages generate specific legal consequences that require special regulatory attention, especially in the areas of citizenship, land ownership, and inheritance. Conclusion: Accordingly, a thorough understanding of applicable legal provisions, combined with proactive legal instruments such as marital agreements and dual-jurisdiction wills, is essential to ensure legal certainty and protection for all parties. This study contributes a cross-regime analysis integrating citizenship, property, and inheritance law—an integrated normative framework that has not previously been synthesized in Indonesian legal scholarship.